Highly active new alpha-diimine nickel catalyst for the polymerization of alpha-olefins - Liu, Hua-Rong; Gomes, P. T.; Costa, S. I.; Duarte, M. T.; Branquinho, R.; Fernandes, A. C.; Chien, J. C. W.; Singh, R. P.; Marques, Maria M. (Journal of Organometallic Chemistry, 2005)
A new silylated alpha-diimine ligand, bis[N,N `-(4-tert-butyl-diphenylsilyl-2,6-diisopropylphenyl)imino]acenaphthene 3, and its corresponding Ni(II) complex, {bis[N,N `-(4-tert-butyl-diphenylsilyl-2,6-diisopropylphenyl)imino]acenaphthene} dibromonickel 4, have been synthesized and characterized. The crystal structures of 3 and 4 were determined by X-ray crystallography. In the solid state, complex 4 is a dimer with two bridging Br ligands linking the two nickel centers, which have square pyramidal geometries. Complex 4, activated either by diethylaluminum chloride (DEAC) or methylaluminoxane (MAO) produces very active catalyst systems for the polymerization of ethylene and moderately active for the polymerization of propylene. The activity values are in the order of magnitude of 10(7) g PE (mol Ni [E] h)(-1) for the polymerization of ethylene and of 10(5) g PP (mol Ni [P] h)(-1) for the polymerization of propylene. NMR analysis shows that branched polyethylenes (PE) are obtained at room or higher temperatures and almost linear PE is obtained at 0 degrees C with 4/DEAC. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: alpha-diimine nickel complex; Ethylene polymerization; late transition-metal; propylene polymerization

Copolymerization of ethylene with unsaturated alcohols and methylmethacrylate using a silylated alpha-diimine nickel catalyst: molecular modeling and photodegradation studies - Matos, Ines; Fernandes, Susete N.; Liu, Hua-Rong; Tevtia, Amit K.; Singh, R. P.; Manda, Lemos; Lemos, Francisco; Marques, Maria M. (Journal of Applied Polymer Science, 2013)
In this article, the experimental results obtained in the copolymerization of ethylene with polar monomers using a silylated -diimine nickel catalyst are described and compared with those obtained with a non-silylate similar one. The results show that the introduction of a siliyl group in the para-position of the imine moiety turns the catalyst less sensitive toward polar functionalities. However, the reactivity observed in copolymerization reactions was found to be reduced both the global polymerization and incorporation rates. Molecular modeling calculation allowed us to understand both the preferred insertion mode and the intermediate product structures for E/MMA copolymerization. Photodegradation studies showed that the presence of polar groups in the copolymers increases their rate of oxidation and turn them more easily degradable. The stabilization performed by Tinuvin 770 showed that for long-exposure times, it is not very effective regardless it is only mixed or grafted to the copolymer. (c) 2012 Wiley Periodicals, Inc.
Keywords: ageing; copolymers; Degradation; grafting